A bibliometric and visualization study of global research trends in sacral Tarlov cyst from 2000 to 2022 - Lu, Yang; Bao, Luyao; Wang, Nan; Chen, Shuang; Qian, Yuzhang; Gu, Jun; Kang, Ran; Xie, Lin (Frontiers in Surgery, 2024)
Background: Symptomatic sacral Tarlov cyst (STC) exerts a significant negative impact on the patient's quality of life, highlighting the significance of the increasing number of studies on STC. However, bibliometric analyses in this research field are scarce. Thus, this study aims to provide a comprehensive knowledge structure and identify the research trends of STC through bibliometrics.Methods: Articles related to STC from 2000 to 2022 were sourced from the Web of Science Core Collection database. VOSviewer 1.6.16, CiteSpace 6.1.6, GraphPad Prism 8.2.1 and R-package 'bibliometrix' were used to analyse the data and generate knowledge maps.Results: A total of 930 studies on STC from 2000 to 2022 were included. The findings revealed a consistent yet upward trend in the number of annual publications in this field.